2014
DOI: 10.1108/jat-09-2012-0021
|View full text |Cite
|
Sign up to set email alerts
|

Empirical studies on the effectiveness of assistive technology in the care of people with dementia: a systematic review

Abstract: Purpose – The purpose of this paper is to assess the empirical support for the use of assistive technology in the care of people with dementia as an intervention to improve independence, safety, communication, wellbeing and carer support. Design/methodology/approach – A total of 232 papers were identified as potentially relevant. Inclusion criteria were: studies published between 1995 and 2011, incorporated a control group, pre-test-post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
109
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(114 citation statements)
references
References 62 publications
5
109
0
Order By: Relevance
“…68,90,91,112,120,133,142 For example, a mixed-methods study 68 on older people with diabetes and a qualitative study 91 on people living with dementia highlight the importance of family carer assistance in the use of AT. Family carers were found to invest a substantial amount of effort in embedding AT to help their relatives to maintain independence and reduce potential risks, which in turn minimises carer anxiety.…”
Section: Resmentioning
confidence: 99%
See 4 more Smart Citations
“…68,90,91,112,120,133,142 For example, a mixed-methods study 68 on older people with diabetes and a qualitative study 91 on people living with dementia highlight the importance of family carer assistance in the use of AT. Family carers were found to invest a substantial amount of effort in embedding AT to help their relatives to maintain independence and reduce potential risks, which in turn minimises carer anxiety.…”
Section: Resmentioning
confidence: 99%
“…A systematic review 90 of AT for people living with dementia (n = 41 studies) found that there is currently little evidence to suggest that AT has an impact on the independence, safety or security of people living with dementia. There was some evidence to support the use of AT to facilitate communication and provide access to support and information for carers.…”
Section: Assistive Technology To Maintain Autonomymentioning
confidence: 99%
See 3 more Smart Citations